Memoir Hailani Muji Tahir : jejak langkah menuju puncak - Hailani Muji Tahir, 1945- (Bangi : Penerbit Universiti Kebangsaan Malaysia, 2013)
Autobiography of Hailani Muji Tahir, an academician on economic and Islamic finance at UKM, Malaysia.
Includes indexes.
Keywords: Hailani Muji Tahir, -- 1945-; Intellectuals -- Malaysia -- Biography